MAMMAL MONITORING IN MEXICO’S FIRST BIOSPHERE RESERVES: MAPIMÍ AND LA MICHILÍA, DURANGO - González Romero, Alberto; Gallina Tessaro, Sonia; López-Tello Mera, Eva (Kuxulkab’, 2024)
Mapimí and La Michilía were the first Biosphere Reserves in Mexico (Durango), established in 1978 with the support of the Institute of Ecology (INECOL). Mapimí represents the ecosystem of the Chihuahuan desert; La Michilía represents the mixed temperate forest ecosystem of the Sierra Madre Occidental. The objective of this work was to monitor medium and large mammals in the two reserves to evaluate their richness and relative abundance index. In Mapimí, 13 species of wild mammals and 2 domestic mammals were identified; in La Michilía, 10 wild mammals, 2 domestic mammals and 2 introduced exotic mammals were identified. Knowing the conservation status of medium and large mammals, using camera traps, allows us to identify which factors may be affecting their presence; for example, cattle ranching could be exerting strong pressure on these ecosystems, as well as exotic species on native species populations.